Kajian Penambahan Unit Ground Control Militer sebagai Optimalisasi Kinerja Air Traffic Controller - Purbo Wartoyo, Bayu; Nuri Sabilah, Liha; Suharyanto; Sulaiman, Ahmad (Politeknik Penerbangan Makassar, 2020)
The Aerodrome Control Tower (YANI TWR) unit is one part of the ATS Unit in Ahmad Yani International Airport Semarang Which is very important in providing Aerodrome Control service services. The responsibilities of Tower Controller include the maneuvering area and the vicinity of an Aerodrome area. As the number of military traffic due to Ahmad Yani Airport is the military enclave airport, it also increases workload a TWR controller, so as to reduce Controller workload and increase the level of service required Improvement of services in the form of the addition of military Ground Control unit at Ahmad Yani Semarang International Airport.